Sun Makes Java Open Source. - Dailey Paulson, Linda (Computer (00189162), 2007)
The article reports on the release of Sun Microsystem's Java technology as an open source software. This is to let programmers examine, modify or add features to Java's underlying code and let users build applications by combining code without making the overall programs available under license. Java technology to be released includes all Java platform and Micro Edition at https://phoneme.dev.java.net. The company's participation in the open source development will result in the release of million of lines of code to the open source community and marks the biggest contribution comparable to Netscape Communication's creation of Mozilla.